2010
DOI: 10.1128/aem.01420-09
|View full text |Cite
|
Sign up to set email alerts
|

Genes Involved in Yellow Pigmentation of Cronobacter sakazakii ES5 and Influence of Pigmentation on Persistence and Growth under Environmental Stress

Abstract: Cronobacter spp. are opportunistic food-borne pathogens that are responsible for rare but highly fatal cases of meningitis and necrotizing enterocolitis in neonates. While the operon responsible for yellow pigmentation in Cronobacter sakazakii strain ES5 was described recently, the involvement of additional genes in pigment expression and the influence of pigmentation on the fitness of Cronobacter spp. have not been investigated. Thus, the aim of this study was to identify further genes involved in pigment exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 52 publications
0
32
0
Order By: Relevance
“…S6). This genetic setting is common to species of the genus Cronobacter (Johler et al, 2010) and was also found in the genomes of Pantoea sp. IMH (Tian & Jing, 2014) and Pantoea sp.…”
mentioning
confidence: 64%
“…S6). This genetic setting is common to species of the genus Cronobacter (Johler et al, 2010) and was also found in the genomes of Pantoea sp. IMH (Tian & Jing, 2014) and Pantoea sp.…”
mentioning
confidence: 64%
“…Southern analysis was performed as described previously (21). For identification of insertion sites by the subcloning procedure, chromosomal DNA of the transposon mutants was digested with SphI, and the fragments were ligated into pUC18NotI (Table 1) digested with the same enzyme.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Edelson-Mammel et al (2006) reported that 10 out of 12 strains showed ,1 log decline at pH 3.5 over a 5 h incubation at 37 u C, whilst the most acid-sensitive strain showed~3.5 log decline. Johler et al (2010) showed that Cronobacter strains not only survived low pH, but were also able to grow to~10 9 c.f.u. ml 21 at pH 4.5 within 24 h. Overall, Cronobacter have a good potency to survive in acidic environments that may enable them to cope with stomach acidity.…”
Section: Desiccation Adaptationmentioning
confidence: 99%